An audit of Cesarean Sections using Robsons Classificationat Provincial Hospital Janakpurdham. - Thakur,Murari (2020)
ABSTRACT: Background: Caesarean Section is the most commonly performed obstetric operation worldwide and has been public health concern.This study aims to categorize all pregnant women admitted for delivery according to Robsonsten group classification and to assess the caesarean section rate and identify the indications contributing to the same. Methods:This was prospective study conducted at Provincial Hospital Janakpurdham for threemonthsfrom15thAprilto15thJuly2020.Totalof1536patientswereincludedinthestudyandwereclassifiedaccordingtotheRobsonsclassification.For each group,we calculated its relative size and its contribution to the overall caesareanrate. Results:Theoverallcaesareansectionratewas16.7%(257among1536totaldeliveries).previous caesarean section,singleton cephalic,>=37weeks(Group5)was the major(7.7%)contributor to the overall caesarean section rate followed byandnullipara,singleton cephalic,>=37weeks,caesarean section before labor(Group2b,2.6%).Labor induction was not done in any case.Conclusion:InductionoflaborforGroup2and4andtrialforvaginaldeliveryinpreviousCesareansectionforGroup5shallbepromotedtoreducethecaesearensectionrate. Keywords:Cesarean section,Robsons assifications.